2016
DOI: 10.18267/j.efaj.160
|View full text |Cite
|
Sign up to set email alerts
|

Does High Growth Create Value for Shareholders? Evidence from S&P500 Firms

Abstract: Abstract:This paper investigates the relationship between growth rate and shareholder value creation, using a sample of 243 non-financial Standard and Poor's 500 (S&P500) companies, which have 22 years of consecutive data available . Sustainable Growth Rate Model (SGR) is used to divide the sample into two groups as high growth firms and moderate growth firms. Using Panel data approach, it is shown that sales growth below sustainable growth rate (SGR) enhance shareholder value at a significantly higher rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This finding is consistent with the existing literature on this phenomenon, and therefore the study does not reject the null hypothesis that firm growth does not affect the shareholders ' wealth of the listed manufacturing companies in Nigeria. These results are consistent with the study of Ataunal, Gurbuz and Aybars (2016) which found that firm growth had a positive impact on the market value of the share.…”
Section: Regression Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the existing literature on this phenomenon, and therefore the study does not reject the null hypothesis that firm growth does not affect the shareholders ' wealth of the listed manufacturing companies in Nigeria. These results are consistent with the study of Ataunal, Gurbuz and Aybars (2016) which found that firm growth had a positive impact on the market value of the share.…”
Section: Regression Resultssupporting
confidence: 92%
“…It is believed that high growth (GWT) creates wealth for shareholders. Firm growth (increase in sales revenue) proliferates the resources of shareholders (Ataunal, Gurbuz & Aybars 2016). For our sample of 51 listed manufacturing firms, we use firm growth as a control variable for robust shareholder wealth.…”
Section: Variable Measurementmentioning
confidence: 99%
“…A mere maximizing growth perhaps may assist the firm to accomplish its short-term goals, but not the long-run objective what they seek to-the 'value-creation' (Ramezani et al 2001). The value-creation maximizes around the sustainable growth rate of an organization and decreases sharply, once actual growth exceeds the sustainable growth rate (Ataünal et al 2016). In conjunction, managers are very concerned about establishing and maintaining a positive overall reputation (Schulz and Flickinger 2018).…”
mentioning
confidence: 99%
“…The Higgins (1977Higgins ( , 1981 basis was applied in many studies. Jarvis et al (1992) used to asses macro equivalent of product portfolio analysis; Vasiliou and Karkazis (2002) applied it on data from the National Bank of Greece, and found that its actual growth exceeded the SGR, and consequently discuss four possible financial strategies to deal with it; Hyytine and Pajarinen (2005) used the SDR to study the relation between firm-level disclosure quality and the availability of external finance to firms in Finland and found that excess growth is associated with the quality of disclosure; Phillips et al (2010) applied the SDG model to investigate the crosssectional variations of financial ratios among privatively held retail companies measured as different growth cycle stages; Jin and Wu (2008) analyzed the contribution of intellectual capital to the firm's sustainable growth ability in the case of the listed companies in China; Pickett (2008) applied SGR model to identify the subtle relationship between marketing and operation efficiencies; Listiani and Supramono (2020) investigated the effect of fixed asset growth on sustainable growth rate and the role of sustainable growth rate in mediating the impact of fixed asset growth rate on firm value; Mubeen et al (2021) examined the SDR model in the case of the non-financial forms from seven emerging markets; Mukherjee and Sen (2019) studied the impact of corporate governance on corporate sustainable growth; Farouq et al (2022) made a SDG on ROA analysis applied in the case of the Saudi Banks; Shao (2018) analyzed the sustainable growth characteristics of China's listed companies in textile and garment industry in the 2008-2011 period, using Wilcoxon signed-rank test in the post-crisis era; Ataunal et al (2016) investigated the relationship between growth rate and shareholder value creation, using a sample of 243 non-financial Standard and Poor's 500 (S&P500) companies and found that sales growth below sustainable growth rate (SGR) enhances shareholder value at a significantly higher rate compared to growth above sustainable growth rate; Akhtar et al ( 2021) investigated the impact of financial leverage on the firm's performance, i.e., sustainable growth (SGR), Tobins Q, return on assets (ROA), return on equity (ROE), and return on sales (ROS) and found inverted U-shaped relationship between financial leverage and performance; Wahyuni and Dino (2016) studied the determinant factors of the sustainable growth rate in the case of manufacturing companies listed on the Indonesia Stock Exchange; Wijaya and Atahau (2021) in their study aimed to determine the effect of profitability on sustainable growth in Malaysian and Indonesian manufacturing firms; Rahim (2017) also investigated the association between firm performance and sustainable growth rate in the case of...…”
Section: Literature Reviewmentioning
confidence: 99%